Digital Responsibility Profile and Online Interaction Awareness of Elementary School Students in the Artificial Intelligence Era - Kukuh Andri Aka; 'Alia Nur Husna Afandi (Universitas Pendidikan Ganesha, 2026)
The development of digital technology and artificial intelligence has made elementary school students increasingly interact with information, digital content, and other users in online spaces. However, children’s familiarity with technology does not necessarily indicate their ability to act responsibly, verify information, respect digital works, and maintain ethical online interactions. This study aims to analyze the profile of digital responsibility and online interaction awareness among elementary school students in the artificial intelligence era and to compare their achievement based on gender. This study employed a descriptive-comparative survey design involving 75 elementary school students from grades 4, 5, and 6. Data were collected using a closed-ended questionnaire consisting of 14 statements covering two main aspects: digital responsibility and online interaction awareness. The content validity of the instrument was examined using Aiken’s V, while internal consistency was analyzed using Cronbach’s Alpha. The data were analyzed descriptively using mean scores, standard deviations, and percentage achievement, while gender-based differences were tested using the Mann–Whitney U test. The findings indicate that students demonstrated stronger online interaction awareness than digital responsibility. The results also reveal gender-based differences, with female students tending to show higher digital responsibility and online interaction awareness than male students. This study concludes that digital character education in elementary schools should be strengthened.